Hubungan Keuangan Pemerintah Pusat Dan Daerah Dalam Penyelenggaraan Jaminan Kesehatan Nasional - Martira, Amelia; Nursadi, Harsanto (Jurnal Hukum & Pembangunan, 2020)
Indonesia’s National Health Security (NHS) has begun since 2014 which give a lot of benefits to people in Indonesia. Access to health care become more easier without giving financial hardship. However, there are some obstacles that Indonesia NHS facing, which one is deficit in pool funding that is not enough to pay the benefits. One of newer solution to overcome this problem is by activating the resources from local government, especially from the funding. Basically, decentralization is the framework of the central and local government relation in Indonesia, by transferring power, authority and financial of health functional assignment to local government. Conversely, since Indonesia NHS is held, there is overlapping of authority and financial between administration of health functional assignment by local government and NHS. Then, it contributes to ineffective and inefficient of NHS. Conclusion: There is a need to rearrange the central and local government relation on decentralization context in order to maximize the role of local government to assure the sustainability of NHS in Indonesia.